If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2=1-4n+3n
We move all terms to the left:
-2-(1-4n+3n)=0
We add all the numbers together, and all the variables
-(-1n+1)-2=0
We get rid of parentheses
1n-1-2=0
We add all the numbers together, and all the variables
n-3=0
We move all terms containing n to the left, all other terms to the right
n=3
| b-(8)=21 | | 9/x=5/300x | | y=5+2+1 | | 5x10=60 | | 2.2h=7.7 | | 4(5x=3x)=14+2(5-2x) | | -6x=24=14+16 | | 7=n+-6 | | 7=n+-3 | | 180-17x+48=0 | | r+354=1.321 | | 3x(5-3)=(x5)-(x2) | | -1=3+4n-2n | | 6x-4=6(x-1)+11 | | 299=2x-1 | | 12-5x=58 | | 6x-4=6(x-1 | | 3x−82/3=x−6 | | 4x-5=44-3x | | |5z-8|=4 | | 7+1x=10 | | 4x-6=57-3x | | 9p/9=54/ | | 3(n+9)=5+(-3) | | 5c–43=c+17 | | 5.3^x=0.6^-x | | (9m+1)(4m+5)=0 | | 7(s+7)+2=9s-6 | | 5x+28=153 | | 2(p-7)-2=3p-4 | | 6(s-1)-9=2 | | ⎪2x+3⎥=7 |